Overhead power lines magnetic field reducing in multi-story building by active shielding means - B. I. Kuznetsov (National Technical University "Kharkiv Polytechnic Institute", 2021)
Aim. Reducing of magnetic flux density of magnetic field in multi-storey building, generated by overhead power lines to the sanitary standards level by active shielding means. The tasks of the work are the synthesis, computer simulation and experimental research of three-circuits system of active shielding, which includes three shielding coils. Methodology. When synthesizing the system of active shielding of magnetic field, are determined their number, configuration, spatial arrangement and of shielding coils as well as the shielding coils currents and resulting magnetic flux density value in the shielding space. The synthesis is based on the multi-criteria game decision, in which the payoff vector is calculated on the basis on quasi-stationary approximation solutions of the Maxwell equations. The game decision is based on the stochastic particles multiswarm optimization algorithms. Results. Computer simulation and experimental research of three-circuit system of active shielding of magnetic field, generated by overhead power lines with phase conductors triangle arrangements in multi-storey building are given. The possibility of initial magnetic flux density level reducing in multi-storey building to the sanitary standards level is shown. Originality. For the first time to reducing of magnetic flux density of magnetic field in multi-storey building the synthesis, computer simulation and experimental research of three-circuit system of active shielding of magnetic field generated by single-circuit overhead power line with phase conductors triangular arrangements carried out. Practical value. Practical recommendations from the point of view of the practical implementation on reasonable choice of the spatial arrangement of three shielding coils of three-circuit system of active shielding of the magnetic field generated by single-circuit overhead power line with phase conductors triangular arrangements in multi-storey building are given.